Antimicrobial activities of aqueous lysate of Acanthamoeba spp. against selected pathogenic bacteria - Nakisah, M.A.; Chandrika, K. (Penerbit Universiti Kebangsaan Malaysia, 2012)
The increasing of infectious diseases and emerging of multi-drug resistant bacteria are worldwide problems that require a search for a new potential drug from various sources including free-living amoebae to overcome these problems. In this study, the aqueous lysates of two isolates of Acanthamoeba viz A. castellanii, a clinical isolate designated as IMR isolate, and Acanthamoeba sp., an environmental isolate designated as SW isolate were tested against two pathogenic bacteria, methicilin resistant Staphylococcus aureus (MRSA) and Staphylococcus aureus. The anti-bacterial test was done using disc diffusion (Kirby Bauer) method to determine the minimum inhibition concentration (MIC) values of the lysates against the bacteria. Twofold dilution series of the Acanthamoeba lysates with concentrations ranging from 0.3 mg/mL to 2.4 mg/mL were used. The measurements of diameter of inhibition zone of the amoeba lysates against each bacterium were compared with the inhibition zone caused by a positive control (chloramphenicol) to analyse the effectiveness of the lysates as anti-bacterial agents. MRSA and S. aureus tested were slightly sensitive to both lysates of Acanthamoeba used in this study to suggest the potential of these lysates as bacterial agents. The data obtained were further confirmed by analysis of bacterial morphology under SEM.